Originalism, federalism, and the American constitutional enterprise : a historical inquiry - Purcell, Edward A. (Yale University Press, 2007)
In this lively historical examination of American federalism, a leading scholar in the field refutes the widely accepted notion that the founding fathers carefully crafted a constitutional balance of power between the states and the federal government. Edward A. Purcell Jr. bases his argument on close analysis of the Constitution's original structure and the ways that structure both induced and accommodated changes over the centuries. There was no clear agreement among the founding fathers regarding the "true" nature of American federalism, Purcell contends, nor was there a consensus on "correct" lines dividing state and national authority. Furthermore, even had there been some true "original" understanding, the elastic and dynamic nature of the constitutional structure would have made it impossible for subsequent generations to maintain any "original" or permanent balance. The author traces the evolution of federalism through the centuries, focusing particularly on shifting interpretations founded on political interests. He concludes with insights into current issues of federal power and a discussion of the grounds on which legitimate decisions about federal and state power should rest.
Keywords: Federal government -- United States.; Constitutional history -- United States.; United States -- Politics and government.; Histoire constitutionnelle -- États-Unis.; États-Unis -- Politique et gouvernement.; BUSINESS & ECONOMICS / General.; Constitutional history; Federal government; Politics and government; United States